Multisensory experiences where the senses meet technology - Velasco, Carlos 1968- (Oxford University Press, 2020)
Multisensory Experiences: Where the senses meet technology takes you on a journey that goes from the fundamentals of multisensory experiences, through the relationship between the senses and technology, to what the future of those experiences may look like, and our responsibility in it